Dentists' perception, knowledge, and clinical management of molar-incisor-hypomineralisation in Kuwait: a cross-sectional study - Abrar Alanzi; Anfal Faridoun; Katerina Kavvadia; Aghareed Ghanim (BMC, 2018)
Abstract Background Molar-incisor Hypomineralisation (MIH) is considered as a global dental problem. There is little knowledge of general dental practitioners (GDPs) and dental specialists (DSs) about this condition in different parts of the world, particularly in Gulf Cooperation Council (GCC) countries. Hence, this study has been carried out to assess the knowledge of GDPS and DSs in Kuwait about MIH condition, its clinical presentation and management. Findings would help national school oral health program (SOHP) to promote good oral healthcare. Methods A structured questionnaire was distributed to 310 attendees of the 18th Kuwait Dental Association Scientific Conference, Kuwait. Data concerning demographic variables, prevalence, diagnosis, severity, training demands and clinical management of MIH were collected. Results A response rate of 71.3% (221/310) was reported. 94% of respondents noticed MIH in their practice. Yellow/brown demarcation has been observed as a common clinical presentation (> 50%). Almost 10-20% of MIH prevalence has been reported by the participants. Resin composite was the dental material often used in treating MIH teeth (~ 65%), and fewer than half would use it for treating moderately affected molars. Most respondents would use preformed metal crowns for severe MIH (63%). Dental journals were the information source for DSs; whereas, the internet was the information source for GDPs. Child's behaviour was the main reported barrier for treatment of MIH affected children. Many GDPs felt unconfident when diagnosing MIH compared to dental specialists. Respondents supported the need to investigate MIH prevalence and to receive a clinical training. Conclusions Molar incisor hypomineralisation is a recognised dental condition by practitioners in Kuwait. Yellow/brown demarcated opacities were the most reported clinical presentation, and the composite resin was the most preferred dental material for restoring MIH teeth. Most GDPs and dental specialists would use preformed metal crowns for severely affected molars. GDPs reported low levels of confidence in MIH diagnosis which necessitates conducting continuing education courses to provide high- quality dental care for children with MIH.